2021
DOI: 10.1007/s13369-021-06000-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TIG Welding Parameters and Automatization for Non-Heat Treated Inconel 718 Sheets

Abstract: Inconel 718 alloy is widely used in applications that require advanced strength properties especially at high temperature conditions. Combust room walls, exhaust parts, jet tribune blades and gas tribune equipment are the most known using areas. This alloy can be welded with various fusion welding methods, but TIG (Tungsten Inert Gas) welding is preferred since, it provides simply application, mobility and low cost. This study was aimed to clarify that how adjusting the welding parameters and welding automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the literature review, it has been reported that spherical and quadrangular precipitates are carbides formed by metals in the material [23]. Nevcanoglu et al [24] stated that metal carbides in the chemical forms of TiC, NbC, CrC, and M23C6 in the weld metal of Inconel 718 superalloys joined by TIG welding can affect the material properties positively or negatively depending on their location. Precipitates in austenite grains prevent the movement of dislocations and increase the strength.…”
Section: Microstructure Resultsmentioning
confidence: 99%
“…In the literature review, it has been reported that spherical and quadrangular precipitates are carbides formed by metals in the material [23]. Nevcanoglu et al [24] stated that metal carbides in the chemical forms of TiC, NbC, CrC, and M23C6 in the weld metal of Inconel 718 superalloys joined by TIG welding can affect the material properties positively or negatively depending on their location. Precipitates in austenite grains prevent the movement of dislocations and increase the strength.…”
Section: Microstructure Resultsmentioning
confidence: 99%
“…Also, TIG welding processes are likely to result in the formation of coarse-grain structures and defects such as porosity, entrapment of impurities, microstructural cracks etc., [9,10]. The high weld temperature cycle that metal goes through during welding is the primary cause of mechanical properties and microstructural variation [11,12]. To overcome such an undesirable phenomenon and to refine the grain size, reinforcing master alloys like Br, Ti, Er, Sc, and Zr to the alloy melts and filler melts have been attempted.…”
Section: Introductionmentioning
confidence: 99%